2013
DOI: 10.1080/07315724.2013.816614
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of Oatmeal on Subjective Measures of Appetite and Satiety Compared to a Ready-to-Eat Breakfast Cereal: A Randomized Crossover Trial

Abstract: Oatmeal improves appetite control and increases satiety. The effects may be attributed to the viscosity and hydration properties of its β-glucan content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 42 publications
3
40
0
Order By: Relevance
“…Thus, vagal nerve stimulation from other regions of the digestive tract, such as stomach and small intestine, are more likely contributors to modulating diet intake, especially when barley b-glucan can increase digesta viscosity in the upper gut (Brockman et al 2012) and tends to slow the rate of gastric emptying (Belobrajdic et al 2015). These observations align with clinical studies which showed that oat b-glucan increased perceptions of satiety during the postprandial period Juvonen et al 2009;Lyly et al 2010;Pentikainen et al 2014;Rebello et al 2013Rebello et al , 2014 and modulated the secretion of satiety hormones in the small intestine, including cholecystokinin, ghrelin and peptide YY Vitaglione et al 2009). Therefore, b-glucan fermentation in the large bowel is unlikely to contribute to reduced energy intake and body weight.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, vagal nerve stimulation from other regions of the digestive tract, such as stomach and small intestine, are more likely contributors to modulating diet intake, especially when barley b-glucan can increase digesta viscosity in the upper gut (Brockman et al 2012) and tends to slow the rate of gastric emptying (Belobrajdic et al 2015). These observations align with clinical studies which showed that oat b-glucan increased perceptions of satiety during the postprandial period Juvonen et al 2009;Lyly et al 2010;Pentikainen et al 2014;Rebello et al 2013Rebello et al , 2014 and modulated the secretion of satiety hormones in the small intestine, including cholecystokinin, ghrelin and peptide YY Vitaglione et al 2009). Therefore, b-glucan fermentation in the large bowel is unlikely to contribute to reduced energy intake and body weight.…”
Section: Discussionsupporting
confidence: 81%
“…The addition of oat bran (4 or 8 g b-glucan) to biscuits and juice increased satiety compared with the control meal without b-glucan, but b-glucan added only to biscuits did not produce this effect [42]. Oatmeal (2.6 g b-glucan) prepared with hot water produced greater viscosity, larger hydration molecules, and increased satiety compared with a ready-to-eat oat-based cereal (1.7 g b-glucan) served with cold milk [43]. In both studies, sufficient hydration of the fiber seemed to facilitate the satiety process [42,43].…”
Section: Recent Findingsmentioning
confidence: 86%
“…Oatmeal (2.6 g b-glucan) prepared with hot water produced greater viscosity, larger hydration molecules, and increased satiety compared with a ready-to-eat oat-based cereal (1.7 g b-glucan) served with cold milk [43]. In both studies, sufficient hydration of the fiber seemed to facilitate the satiety process [42,43].…”
Section: Recent Findingsmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, other studies have suggested that MC4R regulates metabolic and behavioral responses to high-protein and low-fat intake (10). Protein intake is known to increase secretion of gastrointestinal hormones, which are regulated by the MC4R variant (28), and to induce satiety (29), and thereby to sustain reductions in appetite and ad libitum caloric intake (30) and to increase weight loss and prevent weight regain (31). In addition, dietary protein regulates MC4R gene expression (32).…”
Section: Figurementioning
confidence: 99%